Polymerase theta-mediated end joining of replication-associated DNA breaks in C. elegans - Roerink, Sophie F.; van Schendel, Robin; Tijsterman, Marcel

(untitled) (Genome Research, 2014)
DNA lesions that block replication fork progression are drivers of cancer-associated genome alterations, but the error-prone DNA repair mechanisms acting on collapsed replication are incompletely understood, and their contribution to genome evolution largely unexplored. Here, through whole-genome sequencing of animal populations that were clonally propagated for more than 50 generations, we identify a distinct class of deletions that spontaneously accumulate in C. elegans strains lacking translesion synthesis (TLS) polymerases. Emerging DNA double-strand breaks are repaired via an error-prone mechanism in which the outermost nucleotide of one end serves to prime DNA synthesis on the other end. This pathway critically depends on the A-family polymerase theta, which protects the genome against gross chromosomal rearrangements. By comparing the genomes of isolates of C. elegans from different geographical regions, we found that in fact most spontaneously evolving structural variations match the signature of polymerase theta-mediated end joining (TMEJ), illustrating that this pathway is an important source of genetic diversification.